Pengembangan Kompetensi Soft Skills Digital Mahasiswa melalui Workshop Etika AI dan Literasi Teknologi - Desy Sary Ayunda; Sharfina; Novi Sari Liani; Nur Elisyah; Muhammad (Indo Publishing, 2025)
The development of digital technology and the use of artificial intelligence (AI) in education require students to have adequate digital literacy competencies and ethical use of AI. However, various studies show that Indonesian students still face challenges in understanding data security, information verification, and the ethical boundaries of using AI-based technology. This community service activity aims to improve students' digital soft skills through digital literacy and AI ethics workshops, implemented in stages and collaboratively by lecturers from Malikussaleh University, Almuslim University, and the Kebangsaan Islamic University of Indonesia. A total of 100 students participated in the activity, which was divided into three waves to ensure effective interaction and mentoring. The activity methods included an initial survey, digital literacy training, case study-based AI ethics discussions, practices for responsible AI use, and four weeks of intensive mentoring. Evaluation results showed significant improvements in digital literacy, understanding of AI ethics, information verification skills, and digital security awareness. The average student score increased from 58.1 in the pre-test to 83.4 in the post-test, and 76% of participants demonstrated changes in more ethical behavior in using AI. This activity proves that a phased and collaborative training model is effective in strengthening students' digital competencies in the era of artificial intelligence.